PEDAGOGIC STRATEGIES USED FOR REMOTE PHYSICAL EDUCATION CLASSES DURING THE COVID-19 PANDEMIC IN BRAZIL - Patrícia Luna Pinheiro Brasil, Isaline; Ribeiro Luz, Edma; Eric Vale de Sousa, Francisco (Revista Gênero e Interdisciplinaridade, 2023)
The pandemic period of the new coronavirus, the COVID 19, paralyzed the whole world, just as Brazil, due to the virus proliferation and its several consequences, such as the death of those infected by the virus, there were several governmental actions to tackle the epidemic, affecting the economy with the closing of commerce and also affecting the educational sector. In this respect, it is important to remember that during this period there were adaptations in the teaching-learning process, changing the pedagogical practices. While in some Brazilian cities the classes started to be executed through digital platforms, in other places, due to the lack of access to the internet, an apostille system was used, thus causing access and permanence problems for both students and teachers in the education system. The difficulties faced by education professionals, evidenced by teachers, principals and students, and it must be said in passing that the latter were the most affected and forced to adapt to the new measures and adapt to technologies that in turn at that time was a totally unknown environment for everyone. All things considered, although all teachers have faced different difficulties, it is of utmost importance to highlight the teachers of physical education who were undoubtedly also affected and had to reinvent themselves to continue their classes and activities during the pandemic period, since this subject has a theoretical and practical organization. Given this reality, this paper aims to highlight the pedagogical practices and tools used by physical education teachers in the north, northeast, south, southeast and central-west regions of Brazil during the remote classes due to the pandemic of covid-19, for both used the qualitative approach of the bibliographic type having as methodological tool the analysis of articles as a source of research to be able to acquire the results to demonstrate during the development of the bibliographic research. Thus, it was concluded that The teachers used the media and technological tools in their favor to carry out their classes, making the effective participation as much as possible and then being able to notice the progression of their students in relation to the classes even when they were distant from the face-to-face reality that was the classroom.